Reporting of patient journey mapping in current literature: a scoping review protocol. Issue 5 (24th May 2022) - Davies, Ellen L.; Pollock, Danielle; Graham, Amy; Laing, Robert E.; Langton, Vikki; Bulto, Lemma; Kelly, Janet
ABSTRACT: Objective: This scoping review will assess the literature that documents or utilizes patient journey mapping methodologies in health care settings. It will also examine the reporting processes of studies that use this methodology. Introduction: Health care systems are complex and can be challenging for patients to navigate. Using patient journey mapping as a research method promotes a deeper understanding of patient experiences when navigating these systems. Patient journey mapping provides valuable insights into where systems are working well, where gaps in care exist, and how the system could respond to these gaps. Inclusion criteria: This review will consider peer-reviewed articles and publicly available academic literature documenting patient journey mapping methodologies. The review will also consider studies providing guidance and recommendations on how to report patient journey mapping studies in health care services and systems. Methods: The proposed review will follow JBI guidance for scoping reviews. The following databases will be searched: MEDLINE, Embase, Emcare, PsycINFO, Scopus, Web of Science Core Collection, the Directory of Open Access Journals, Informit, and ProQuest Dissertations and Theses Global. The search will not be limited to year of publication but will be limited to studies reported in English. The PRISMA-ScR extension will be used to document the literature search. Two reviewers will screen titles, abstracts, and full-text articles. An extraction table will be used to extract relevant data from all included articles and to facilitate data analysis.